Therapeutic Azithromycin Mitigated Monosodium Glutamate-Related Dysfunction in Rats’ Body Weight and Serum, Liver, Kidney and Heart Antioxidant Defense Bioindicators - Egbuonu, Anthony Cemaluk Chinedum; Alaebo, Prince Ogochukwu; Onuoha, Udumma Nsofor; Njoku, Chinomso Juliet; Eze, Obioma Benedeth; Odoemelam, Francisca Ugochi; Edum, Michael Eberechukwu; Obi, Ojichukwu Boniface; Ukaegbu, Mmesoma Joy; Nwaogwugwu, Sandra Uchechi; Orji, Marvellous Chinonso; Ndukwe, Clara Ngozika; Opara, Prosper; Oyoyo, Chinagorom; Joe-Eme, Chika Blessing; Okwoigwe, Cheluchiaka Jecinta (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Monosodium glutamate (MSG) mediates body weight gain (BWG) and oxidative stress. Azithromycin (AZT), may be abused and co-consumed with MSG to present unknown outcomes on BWG and oxidative stress. This study evaluated the effect of AZT and MSG in rats’ BWG and antioxidant bioindicators. Thirty rats assigned to five groups were orally exposed for seven consecutive days to groups A, control (distilled water, 1 ml/kg), B, MSG (MSG 8000 mg/kg), C, therapeutic AZT, TAZ (AZT 82.5 mg/kg), D, overdose AZT, OAZ (AZT 412.5 mg/kg) and E, TAZ + MSG (AZT 82.5 mg/kg + MSG 8000 mg/kg). MSG-treated rats exhibited a significantly (p < 0.05) increased BWG; serum, liver, kidney and heart reduced glutathione (GSH), glutathione peroxidase (GPX), superoxide dismutase (SOD), and malondialdehyde (MDA) but decreased catalase (CAT) and zinc (Zn) levels compared to control. Co-treated TAZ + MSG rats significantly (p < 0.05) decreased BWG, GSH, GPX, SOD, Zn; increased CAT and non-significantly (p > 0.05) decreased MDA compared to MSG and control. Thus, TAZ significantly mitigated BWG, and malfunction in the metabolism of antioxidant defense bioindicators in MSG rats via probable anorexigenic, anti-inflammatory and antioxidant responses. This suggests that TAZ could be useful in managing MSG-related dysfunction in BWG and metabolic activity of the antioxidant defense apparatus in rats.